Hybrid selection for sequencing pathogen genomes from clinical samples - Melnikov, Alexandre; Galinsky, Kevin; Rogov, Peter; Fennell, Timothy; Van Tyne, Daria; Russ, Carsten; Daniels, Rachel; Barnes, Kayla G; Bochicchio, James; Ndiaye, Daouda; Sene, Papa D; Wirth, Dyann F; et al. (Genome biology, 2011)
We have adapted a solution hybrid selection protocol to enrich pathogen DNA in clinical samples dominated by human genetic material. Using mock mixtures of human and Plasmodium falciparum malaria parasite DNA as well as clinical samples from infected patients, we demonstrate an average of approximately 40-fold enrichment of parasite DNA after hybrid selection. This approach will enable efficient genome sequencing of pathogens from clinical samples, as well as sequencing of endosymbiotic organisms such as Wolbachia that live inside diverse metazoan phyla.